Looking back to move forward: shedding light on the dark side of entrepreneurship. (2024)
Purpose – While entrepreneurship has long been heralded for its positive contributions, there is a growing recognition of its “dark side,” characterized by unproductive, unethical and destructive actions. This exploratory literature review aims to illuminate the underexplored dark side of entrepreneurship, thereby enriching the discourse on entrepreneurship’s dual nature. Design/methodology/approach – This study employs a robust mixed-method approach, integrating phenomenologically detailed co-citation bibliographic coupling with detailed thematic data and code-weaving. Science mapping tools like R-Bibliometrix and VOSviewer enhance the credibility of the findings by providing a sophisticated and reproducible methodological framework. Findings – This review defines dark entrepreneurship, its characteristics, and its complexities. We introduced the “Dark Entrepreneurship Trinity”: Ethical Complexity, Institutional Navigation and Conflict Entrepreneurialship, with Institutional Navigation as the apex theme. It elucidates how this theme influences ethical dilemmas and operational strategies in conflict zones, illustrated through a diagram depicting their complex interrelations and dynamics. Originality/value – The originality of this literature review lies in its comprehensive synthesis of the dark side of entrepreneurship. This review significantly contributes to the academic discourse by delineating a clearer picture of the destructive potentials of entrepreneurship. It compiles existing research, critically addresses the gaps and suggests future pathways for empirical studies.